Back-compatible Color QR Codes for colorimetric applications. (January 2023) - Benito-Altamirano, Ismael; Martínez-Carpena, David; Casals, Olga; Fábrega, Cristian; Waag, Andreas; Prades, Joan Daniel
Highlights: Color correction often relies on color charts that can accomodate limited colors (10 s). QR Codes can be used to accomodate a large number of color samples (1000 s). QR Code have compact form factor (a few inches) while chart have a wide factor form. Our grayscale affinity to black and white during color mapping is fully back-compatible. Grayscale method leads to much higher readability in adversarial opticial conditions. Abstract: Color correction techniques in digital photography often rely on the use of color correction charts, which require including this relatively large object in the field of view. We propose here to use QR Codes to pack these color charts in a compact form factor, in a fully compatible manner with conventional black and white QR Codes; this is, without losing any of their easy location, sampling and digital data storage features. First, we present an algorithm to build these new colored QR Codes that preserves the original QR Code functionality - much more than other coloring proposals based on the random substitution of black and white pixels by colors - that relies on the ability of the native CRC code to correct and counteract these alterations. Second, we demonstrate that, as a result, these QR Codes can allocate far many more colors than the conventional color correction charts, enabling much more accurate color correction schemes in a more convenient and usable format.